MENUMBUHKAN SIKAP KEPEDULIAN LINGKUNGAN MELALUI MODEL PEMBELAJARAN PJBL BERBASIS STEAM PADA MATA PELAJARAN MUATAN LOKAL DAS & DANAU KELAS V - Alya Datunsolang; Razak H. Umar; Aris Iskandar (Al-mujahidah, 2026)
This research is motivated by the main problem, "Can the application of the STEAM-based PjBL learning model foster environmental awareness among fifth-grade students of SDN 24 Limboto?" The purpose of this study is to determine whether the application of the STEAM-based PjBL model can foster environmental awareness among fifth-grade students of SDN 24 Limboto. This study uses the classroom action research (CAR) method, with data collection techniques in the form of observation, questionnaires, and documentation. The object of this study is the environmental awareness of students, which is to be fostered through the application of the STEAM-based Project Based Learning (PjBL) learning model in the Local Content subject of DAS & Danau. The subjects of this study were 14 fifth-grade students of SDN 24, consisting of 9 boys and 5 girls. The results of the study showed that an increase in the percentage of students who reached the caring category when carrying out actions in cycle I, the percentage value was 79.28% and in cycle II, there was an increase with a percentage value of 99.40% and had reached the desired level of success. Based on these findings, it can be concluded that the application of the STEAM-based PjBL model can foster an attitude of environmental concern among fifth-grade students of SDN 24 Limboto.